Wage cyclicality under different regimes of industrial relations - Hermann Gartner; Thorsten Schank; Claus Schnabel (Institute for the Study of Labor (IZA), 2010)
Since there is scant evidence on the role of industrial relations in wage cyclicality, this paper analyzes the effect of collective wage contracts and of works councils on real wage growth. Using linked employer-employee data for western Germany, we find that works councils affect wage growth only in combination with collective bargaining. Wage adjustments to positive and negative economic shocks are not always symmetric. Only under sectoral bargaining there is a (nearly symmetric) reaction to rising and falling unemployment. In contrast, wage growth in establishments without collective bargaining adjusts only to falling unemployment and is unaffected by rising unemployment.
Keywords: J31; E32; J53; 330; wage cyclicality; wage bargaining; works council; Germany; Reallohn; Konjunktur; Tarifpolitik; Mitbestimmung; Arbeitsbeziehungen; Schätzung; Deutschland